2022
DOI: 10.3389/fpsyg.2021.670533
|View full text |Cite
|
Sign up to set email alerts
|

Massive Open Online Course Study Group: Interaction Patterns in Face-to-Face and Online (Facebook) Discussions

Abstract: Interaction has been regarded as a key design component in online and distance learning. In this study, we convened a student-led, blended mode (face-to-face and online/Facebook discussions) massive open online course (MOOC) study group to facilitate interactions for learning. Multiple data, including voice recordings, one-on-one interviews, video recordings, and artifacts were collected and analyzed to detect patterns of interaction in both face-to-face and online/Facebook settings, as well as student percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…For example, in discussion forums there are usually a large number of participants which makes the interpersonal closeness less, whereas in one-to-one interactions the interpersonal closeness would be high. Interactions usually occurred in the form of messages in discussion forums (Gillani and Eynon, 2014;Kellogg et al, 2014;Manli, 2014;Barak et al, 2016;Sunar et al, 2017;Zhang et al, 2017;Shi et al, 2019;Xu et al, 2019;Anderson et al, 2020;Yang and He, 2022), in groups (Su et al, 2016;Wichmann et al, 2016;Zhang et al, 2016;Mayende et al, 2017;Krasny et al, 2018;Sanz-Martínez et al, 2019;Razmerita et al, 2020;Gamage, 2021;Gamage and Whiting, 2021;Pin-Ju and Chen, 2022) or one-to-one with another peer (Bouchet et al, 2017;Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in discussion forums there are usually a large number of participants which makes the interpersonal closeness less, whereas in one-to-one interactions the interpersonal closeness would be high. Interactions usually occurred in the form of messages in discussion forums (Gillani and Eynon, 2014;Kellogg et al, 2014;Manli, 2014;Barak et al, 2016;Sunar et al, 2017;Zhang et al, 2017;Shi et al, 2019;Xu et al, 2019;Anderson et al, 2020;Yang and He, 2022), in groups (Su et al, 2016;Wichmann et al, 2016;Zhang et al, 2016;Mayende et al, 2017;Krasny et al, 2018;Sanz-Martínez et al, 2019;Razmerita et al, 2020;Gamage, 2021;Gamage and Whiting, 2021;Pin-Ju and Chen, 2022) or one-to-one with another peer (Bouchet et al, 2017;Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, de Moura et al (2021) indicated that he blended mode MOOC can improve the quality problems of MOOCs. Chen and Chen (2021) found that MOOC-based blended learning designs was helpful for providing help and resolving problems.…”
Section: Literature Reviewmentioning
confidence: 99%